H-RADIC: A Fault Tolerance Framework for Virtual Clusters on Multi-Cloud Environments - Royo, Ambrosio (2018)
Even though the cloud platform promises to be reliable, several availability incidents prove that it is not. How can we be sure that a parallel application finishes it´s execution even if a site is affected by a failure? This paper presents H-RADIC, an approach based on RADIC architecture, that executes parallel applications protected by RADIC in at least 3 different virtual clusters or sites. The execution state of each site is saved periodically in another site and it is recovered in case of failure. The paper details the configuration of the architecture and the experiment´s results using 3 clusters running NAS parallel applications protected with DMTCP, a very well-known distributed multi-threaded checkpoint tool. Our experiments show that by adding a cluster protector it will be possible to implement the next level in the hierarchy, where the first level in the RADIC hierarchy works as an observer at a site level. In adition, the experiments showed that the protection implementation is out of the critical path of the application and it depends on the utilized resources.